The efficacy of Telegram Messenger as a tool for enhancing argumentative writing among students in open and distance learning - Md Yusof, Nazirah; Abdullah, Amelia (AAOU journal, 2025)
PurposeThis paper explores the effectiveness of using Telegram Messenger as a tool to enhance argumentative writing skills among open and distance learning (ODL) students. The paper outlines that argumentative writing is a crucial skill, particularly in written discourse, and that teaching it to ODL students presents unique challenges compared to traditional classroom settings.Design/methodology/approachThis quasi-experimental study was conducted on first-year ODL students in a Malaysian tertiary institution to measure the effectiveness of using Telegram Messenger to improve argumentative writing skills. The study used convenient sampling, with pre- and post-tests administered to both control and experimental groups, and the results were analyzed using paired sample t-tests. Additionally, qualitative data were gathered from six selected students, ensuring rigorous analysis and elimination of confounding variables by assigning the same writing tasks to all participants.FindingsThe findings of this paper suggest that students in the experimental group showed significant improvement in their argumentative writing skills, as evidenced by higher post-test scores compared to the control group. Qualitative feedback from selected students indicated that Telegram Messenger encouraged participation and made the writing process more engaging and interactive.Research limitations/implicationsThe study involved a relatively small sample size of 60 students from two cases and lasted only 10 weeks. Thus, the findings might not be generalizable to all ODL students. A longer study duration will provide findings on the long-term effects of using Telegram Messenger on argumentative writing skills. Factors such as age, educational background, language proficiency and prior experience in online learning could yield different results.Practical implicationsFor educators and institutions involved in online education, this research highlights the potential of integrating digital platforms like Telegram Messenger into their teaching strategies to enhance student engagement and learning outcomes, particularly in areas such as writing skills development. It also underscores the importance of adapting teaching methods to suit the unique needs and challenges of ODL students. Moreover, incorporating Telegram in ODL writing classrooms can foster a dynamic, interactive environment that supports both individual and collaborative learning.Social implicationsODL has become increasingly popular, especially with the rise of digital communication platforms. This study delves into how such platforms, like Telegram Messenger, can be utilized to enhance the learning experience for ODL students. By leveraging technology, educational opportunities can potentially be extended to individuals who may not have access to traditional classroom settings due to geographical, financial or other constraints.Originality/valueThe originality and value of this study lie in its focus on using Telegram Messenger, a widely accessible and familiar digital platform, to address the unique challenges ODL students face in developing argumentative writing skills in ODL. By employing a quasi-experimental design with both quantitative and qualitative analyses, the study provides robust evidence of Telegram’s effectiveness as a tool to improve engagement and writing outcomes, distinguishing it from traditional methods and other digital platforms that may lack the immediacy or interactivity Telegram offers.